Stimuli-responsive Nano/Biomaterials for Smart Drug Delivery in Cardiovascular Diseases: Promises, Challenges and Outlooks - Vosoughi, Pegah; Naghib, Seyed Morteza; Mozafari, M.R. (Current Medicinal Chemistry, 2025)
Cardiovascular Diseases (CVDs) are responsible for the highest number of deaths and disabilities globally. Although numerous therapeutic options exist for treating CVDs, most traditional strategies have proven ineffective in halting or significantly slowing disease progression, often leading to unfavorable side effects. Using nanocarriers represents an innovative strategy for treating CVD, enabling the personalized delivery of medications to precise locations within the cardiovascular system. Despite significant advancements in pharmacological treatments, challenges persist in effectively administering drugs to the CV system. Employing nanocarriers represents an innovative strategy for treating CVD, enabling the tailored administration of medications to precise locations within the cardiovascular system. Various studies have determined the future outlook of nanomedicines for clinical applications as nanocarrier design continues to improve, leading to enhanced drug delivery and treatment outcomes. The article focuses on the delivery systems of drugs that are effective strategies for treating cardiovascular diseases. This manuscript also seeks to explore new possibilities for how the emerging concept of nanotherapeutics could revolutionize our traditional diagnostic and treatment methods in the coming years.
Keywords: nanostructures